PAN's Political Communication on Instagram: Analyzing Celebrity Politicians' Messages - Alvin, Silvanus (HM Publisher, 2023)
The 2024 general election in Indonesia carries significant importance as it provides the nation with an opportunity to exercise its democratic rights and actively participate in shaping the country's political landscape. As the cornerstone of Indonesia's Unitary State, the election mandates direct, public, free, confidential, honest, and fair representation based on Pancasila and the 1945 Constitution. This study focuses on Partai Amanat Nasional (PAN), one of the prominent political parties participating in the election, and examines its political communication strategies on Instagram. The research delves into the content and style of Instagram posts made by PAN's celebrity politicians, who have backgrounds in the entertainment industry. By employing content analysis, the study identifies three types of messages conveyed by these celebrity politicians: political messages, political events, and non-political messages. The analysis uncovers PAN's efforts to establish a dynamic online presence and engage with the audience through a diverse content mix. Furthermore, the research explores the unique characteristics of Instagram Reels, which constitute the majority of PAN's posts, and their alignment with the short attention spans of netizens. Reels offer a powerful communication channel for politicians to connect with their audience and disseminate their political messages effectively.